POTENSI WISATA DI KAMPUNG NELAYAN BERDASI KOTA BALIKPAPAN, KALIMANTAN TIMUR - Febby Rio Pratama Syarif; Yogiana Mulyani; Nurvita Opu, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Kampung Nelayan Berdasi in Balikpapan, East Kalimantan has promising tourism to be developed. The year 2022 is a turning point for tourism development which was stopped during the pandemic. This area is build in 2018 and have no earlier studies about potential mapping of tourism development. Through this research, tourism potential and analysis of tourism development can be identified. This area have mangrove landscapes and fishing pond is the main selling point of tourism attraction. By using interview and SWOT analysis, found that this area have many tourism attraction such as sailing, bekantan, sunset, traditional fisherman activities, soft shell crab, fishing, and studies of ecotourism and edutourism. There is no tourism group in the area to make more community involment. Tourism group is good for the sustainability of the tourist area to maximize its potential in order to improve the community's economy, protect the environment, and the social condition of the community.